Association of Physical Activity Level, Income and Environmental Factors Among Chinese Adults - Dong, Jingjuan; Liu, Wei (Frontiers in Public Health, 2022)
Based on the perspective of residents' income and environmental factors, through the empirical study of the survey data, it is found that: (1) after controlling for the relevant variables, residents' income has a positive impact on residents' participation in physical activities, and the regression coefficient is 0.541 (P <.01) (2) In the regression model after adding environmental variables, the regression coefficient of environmental variables increased from 0.401 (P <. 01) to the highest 1.32 (P <. 01)(3) Through the comparison of the KHB decomposition method, the intermediary effect of residents' income on environmental factors and participation in physical activities is 0.134 (P <. 01), and the intermediary effect ratio is 27.01%. Suggestions: first, the government and society should actively provide public goods needed for physical activities to meet the needs of residents for physical activities; second, the government should strengthen the supply of sports facilities in residential areas, speed up the transformation of villages in cities and improve the living conditions in residential areas; third, through legislation to protect residents' income, improving income is not only to give citizens enough sense of security and happiness but also a way to improve residents' participation in physical activities.